Sistem Penataan Arsip Dalam Menunjang Tertib Administrasi Pada Sekolah Menengah Pertama SMP Negeri 1 Taliabu Barat Laut Provinsi Maluku Utara - Asrudin, Nooraini; Batara, Suriyani Bunga; Nurjannah, Nurjannah (REZ PUBLICA, 2021)
The research objektives are (1) to find out the mechanism of how the archival arrangement system supports administrative order at the SMP Negeri 1 taliabu Laut Barat North Maluku Province, while the dimensions of the archive arrangement system studied include (a) archive organization, (b) systems and procedures file filing, (c) the classification pattern of the archives used, (d) the equipment used, (e) archive storage, (f) borrowing and recovering archives, to (2) to determine the orderly implementation of administration at the SMP Negeri 1 Taliabu Northwest, North Maluku Province. The results show that the archival arrangement system at SMP Negeri 1 Taliabu,  Northwest Maluku Province, is seen from the dimensions: archival organization, system and procedures for filing archives, archival classification patterns used, equipment used, archive storage, borrowing and re-discovering archives, archiving archives. The majority of informants said that in the process of storing, structuring and re-discovering archivest, it was  still not carried out properly, due to the lack of human resources in the implementation of archival storage with a qualification, so that archive storage had not been implemented optimally. Thus, it can be concluded that the archive management system at the SMP Negeri 1 Taliabu Laut Barat is still very minimal and there are no administrative employees with archiving undergraduate qualifications.